The study of entrepreneurship program among the student of Bachelor in Office System Management UiTM Jengka Pahang / Erma Sofhyana Mohammad Nasir - Mohammad Nasir, Erma Sofhyana (2013)
The research entitled "The Study of Entrepreneurship Program among the student of Bachelor in Office System Management UiTM Jengka, Pahang". There are two objectives highlighted in this study which are to analyze the entrepreneurial intentions of Bachelor in Office System Management students in UiTM Jengka, Pahang and to determine the perception about entrepreneurship program among Bachelor in Office System Management students in UiTM Jengka, Pahang. The scope of the study was concentrated on intention of entrepreneurship program among Bachelor in Office System Management students from semester two until five. The researcher used descriptive research as research design and the sampling technique is stratified sampling technique. This study more focused to students from Bachelor in Office System Management students and 140 respondents was selected to fulfill and completed the questionnaires. At the end of the findings, several recommendations have been made for the UiTM and students itself.